Investigating the mechanistic basis of biomechanical input controlling skeletal development: exploring the interplay with Wnt signalling at the joint - Rolfe, Rebecca; Murphy, Paula (University of Edinburgh (datashare), 2018)
Embryo movement is essential to the formation of a functional skeleton. Using mouse and chick models, we previously showed that mechanical forces influence gene regulation and tissue patterning, particularly at developing limb joints. However, the molecular mechanisms that underpin the influence of mechanical signals are poorly understood. Wnt signalling is required during skeletal development and is altered under reduced mechanical stimulation. Here, to explore Wnt signalling as a mediator of mechanical input, the expression of Wnt ligand and Fzd receptor genes in the developing skeletal rudiments was profiled. Canonical Wnt activity restricted to the developing joint was shown to be reduced under immobilization, while overexpression of activated b-catenin following electroporation of chick embryo limbs led to joint expansion, supporting the proposed role for Wnt signalling in mechanoresponsive joint patterning. Two key findings advance our understanding of the interplay between Wnt signalling and mechanical stimuli: first, loss of canonical Wnt activity at the joint shows reciprocal, coordinated misregulation of BMP signalling under altered mechanical influence. Second, this occurs simultaneously with increased expression of several Wnt pathway component genes in a territory peripheral to the joint, indicating the importance of mechanical stimulation for a population of potential joint progenitor cells. This article is part of the Theo Murphy meeting issue ‘Mechanics of Development’.
Roles of Skeletal Muscle in Organ Development
PUBLISHED
Keywords: Transgene expression; Electroporation; Joint formation; Wnt signalling; Molecular mechanisms; Mechanical forces; Developmental Biology